Study on Data center and Data Librarian Role for Reuse of Research Data - Kim, Suntae; Choi, Myung-Seok (2016 8TH INTERNATIONAL CONFERENCE ON KNOWLEDGE AND SMART TECHNOLOGY (KST), 2016)
here are new demands for data centers and data librarians to manage and reuse data. In this study, trends of advanced research institutions were investigated and analyzed and implications were derived, in relation to the environment establishment for management, preservation and reuse of research data generated from research processes. New roles required of data centers and data librarians and 5 roles of data librarians that should be performed as a data scientist were proposed: 1) IDR Manager, 2) Policy Maker, 3) DMP Consultant, 4) Data Consultant and 5) Data Publisher.